The Polar Fox Lagoon in Siberia harbours a community of Bathyarchaeota possessing the potential for peptide fermentation and acetogenesis - Tom Berben; Franco Forlano Bó; Michiel H. in ‘t Zandt; Sizhong Yang; Susanne Liebner; Cornelia U. Welte (Antonie van Leeuwenhoek, 2022)
Archaea belonging to the phylum Bathyarchaeota are the predominant archaeal species in cold, anoxic marine sediments and additionally occur in a variety of habitats, both natural and man-made. Metagenomic and single-cell sequencing studies suggest that Bathyarchaeota may have a significant impact on the emissions of greenhouse gases into the atmosphere, either through direct production of methane or through the degradation of complex organic matter that can subsequently be converted into methane. This is especially relevant in permafrost regions where climate change leads to thawing of permafrost, making high amounts of stored carbon bioavailable. Here we present the analysis of nineteen draft genomes recovered from a sediment core metagenome of the Polar Fox Lagoon, a thermokarst lake located on the Bykovsky Peninsula in Siberia, Russia, which is connected to the brackish Tiksi Bay. We show that the Bathyarchaeota in this lake are predominantly peptide degraders, producing reduced ferredoxin from the fermentation of peptides, while degradation pathways for plant-derived polymers were found to be incomplete. Several genomes encoded the potential for acetogenesis through the Wood-Ljungdahl pathway, but methanogenesis was determined to be unlikely due to the lack of genes encoding the key enzyme in methanogenesis, methyl-CoM reductase. Many genomes lacked a clear pathway for recycling reduced ferredoxin. Hydrogen metabolism was also hardly found: one type 4e [NiFe] hydrogenase was annotated in a single MAG and no [FeFe] hydrogenases were detected. Little evidence was found for syntrophy through formate or direct interspecies electron transfer, leaving a significant gap in our understanding of the metabolism of these organisms.